Confined-range sulfur material, preparation method thereof and application of limited-range sulfur material in lithium metal battery
By confining the sulfur chain inside single-wall carbon nanotubes, the internal resistance problem of sulfur element in lithium metal batteries is solved, and the battery internal resistance is achieved is achieved, which is higher conductivity and stability, and the battery cycle life is extended.
Patent Information
- Application Number
- CN202510085257.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
In existing lithium metal batteries, the insulation and solubility of sulfur element lead to an increase in battery internal resistance, affecting battery life and performance.
By confining the sulfur chain within the single-wall carbon nanotube, a domain-limiting sulfur material is formed to avoid the dissolution and shuttle effects of sulfur, and induce the formation of LiF-rich hybrid SEI.
It improves the conductivity and stability of lithium metal batteries, extends the cycle life of the battery, and improves the lithium transmission capacity.
Smart Images

Figure CN119905593A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a confined sulfur material and a preparation method thereof and application in lithium metal batteries. Background Art
[0002] Lithium dendrite growth and lithium / electrolyte interface side reactions are the main issues affecting the cycle stability and safety of lithium metal batteries. Using materials with excellent lithium affinity and high lithium ion conductivity to modify the copper foil surface can induce lithium metal to deposit evenly on the electrode, thereby inhibiting the growth of lithium dendrites; in addition, the inorganic hybrid SEI (such as LiF, Li2S, LiN) induced by the modified materials can stabilize the lithium metal negative electrode and avoid the loss of active lithium leading to premature battery failure.
[0003] It is currently reported that adding sulfur or lithium polysulfide can induce the uniform deposition of lithium and the formation of LiF-rich inorganic SEI. However, since sulfur itself has insulating properties, direct use increases the internal resistance of the battery, which affects the battery life and performance; and sulfur and its lithium polysulfide are easily soluble in ether electrolytes and undergo a shuttle effect, resulting in the inability to effectively and uniformly catalyze the formation of LiF-rich inorganic SEI. Therefore, it is necessary to find a confined method to inhibit the dissolution and shuttle effect of sulfur and improve its conductivity.
[0004] Therefore, the present invention proposes a confined sulfur material and a preparation method thereof and application in a lithium metal battery. Summary of the invention
[0005] The purpose of the present invention is to provide a confined sulfur material and a preparation method thereof and application in a lithium metal battery to solve the problems in the background technology, and to apply the prepared confined sulfur material to a lithium metal battery to improve the conductivity and stability of the battery.
[0006] To achieve the above objectives, the present invention provides a confined sulfur material, comprising a single-walled carbon nanotube and a sulfur chain within the single-walled carbon nanotube; wherein the sulfur chain is formed by linear connections between single sulfur atoms, and the mass of the sulfur chain accounts for 3 to 10% of the single-walled carbon nanotube.
[0007] The present invention also provides a method for preparing the above-mentioned confined sulfur material, comprising mixing elemental sulfur powder and single-walled carbon nanotube powder, subjecting the mixture to a primary annealing treatment under high vacuum, taking it out and subjecting it to a secondary annealing treatment in a protective gas, and cooling it to obtain the confined sulfur material.
[0008] Preferably, during the primary annealing treatment, the vacuum degree is 1 to 9×10 -3 pa, annealing temperature is 500-700°C, heating rate is 1-10°C / min, and annealing time is 24-60h.
[0009] Preferably, during the secondary annealing treatment, the protective gas is an inert gas, and the flow rate of the protective gas is 20 to 70 sccm; the annealing temperature is 150 to 200° C., the heating rate is 1 to 10° C. / min, and the annealing time is 5 to 20 hours.
[0010] The present invention also provides application of the above confined sulfur material in lithium metal batteries.
[0011] Preferably, the confined sulfur material is used to prepare a lithium metal negative electrode, which includes a negative electrode current collector and a negative electrode active material layer loaded on the surface of the negative electrode current collector, and the raw materials for preparing the negative electrode active material layer include the confined sulfur material, a binder and an organic solvent.
[0012] Preferably, the negative electrode current collector is a copper foil current collector; the binder is polyvinylidene fluoride; and the organic solvent is N-methylpyrrolidone.
[0013] Preferably, the mass ratio of the confined sulfur material to the binder is 3 to 5:1; the mass ratio of the confined sulfur material to the organic solvent is 5 to 10:1.
[0014] Preferably, the preparation method of the lithium metal negative electrode is: mixing the confined sulfur material, a binder and an organic solvent to obtain a slurry; coating the slurry on the surface of the negative electrode current collector, and obtaining the lithium metal negative electrode after drying.
[0015] Preferably, the coating thickness of the slurry is 20 to 100 μm; the drying temperature is 60 to 90° C., and the drying time is 8 to 15 hours.
[0016] In the present invention, the sulfur chain has a strong affinity with Li, which can eliminate the interface energy barrier between Li and the substrate, thereby reducing the nucleation barrier of Li; the sulfur chain is confined inside the single-walled carbon nanotube, does not change the electronic conductivity of the carbon tube, and avoids the increase of battery impedance; the sulfur chain can induce the formation of LiF-rich hybrid SEI, LiF has the characteristics of electronic insulation and lithium ion conduction, and has high mechanical strength, avoiding the occurrence of lithium metal / electrolyte interface side reactions. The sulfur chain is confined inside the single-walled carbon nanotube, avoiding dissolution and shuttle effects, and can stably and efficiently induce the generation of LiF hybrid SEI.
[0017] The confined sulfur composite material provided by the present invention is used as a negative electrode active material of a lithium metal battery, has strong lithium transmission capacity, high coulombic efficiency of the battery, and long cycle life. The preparation method of the confined sulfur composite material provided by the present invention has simple process, simple operation, green and environmental protection, and is suitable for industrial production.
[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Transmission electron microscopy image of the confined sulfur material obtained in Example 1
[0020] Figure 2 The optical morphology comparison diagram of deposited lithium in Example 1 and Comparative Example 2, wherein a is Example 1; b is Comparative Example 2;
[0021] Figure 3 The scanning electron microscope morphology comparison of the deposition and stripping of lithium in Example 1 and Comparative Example 2, wherein a and c are in Example 1; b and d are in Comparative Example 2;
[0022] Figure 4 The figure is a comparison of the electrochemical performance of the lithium metal battery prepared in Example 1 and Comparative Example 2, wherein a is the coulombic efficiency of a button half-cell, b is the time-voltage curve of a button symmetrical battery, c is a cycle performance test diagram of a button full-cell, d is a physical diagram of a soft-pack battery, e is a cycle test diagram of a lithium iron phosphate soft-pack battery, and f is a cycle test diagram of a ternary soft-pack battery;
[0023] Figure 5 The SEI components of Example 1 and Comparative Examples 1 and 2 are compared, and the time-of-flight secondary mass spectra are shown;
[0024] Figure 6 For the comparison of SEI composition between Example 1 and Comparative Examples 1 and 2, the element content was tested by deep XPS. DETAILED DESCRIPTION
[0025] The present invention provides a confined sulfur material, comprising a single-walled carbon nanotube and a sulfur chain in the single-walled carbon nanotube; the diameter of the single-walled carbon nanotube is 1 to 3 nm; the mass of the sulfur chain accounts for 3 to 10% of the mass of the single-walled carbon nanotube, preferably 3 to 8, more preferably 4 to 5%, and further preferably 5%.
[0026] The present invention also provides a method for preparing the above confined sulfur material, comprising the following steps:
[0027] S1. Mixing elemental sulfur powder and single-walled carbon nanotubes, wherein the mass ratio of elemental sulfur powder to single-walled carbon nanotubes is 10-20:100.
[0028] In the present invention, mixing is preferably stirring mixing. The present invention has no particular limitation on the conditions for stirring mixing, as long as the raw materials can be mixed uniformly.
[0029] S2. Performing a first annealing treatment on the mixed powder under high vacuum.
[0030] In the present invention, the vacuum degree ranges from 1 to 9×10 -3 pa, preferably 3×10 -3pa; annealing time is 24 to 60 hours, preferably 40 to 50 hours, more preferably 48 hours. Annealing temperature is 500 to 700°C, preferably 600-800°C, more preferably 650°C. The heating rate from room temperature to the annealing temperature is 1 to 10°C / min, preferably 5°C / min.
[0031] S3, taking out the annealed powder, cooling it and placing it in a tube furnace, performing secondary annealing in a protective gas, and cooling the annealed material to room temperature to obtain a confined sulfur composite material.
[0032] In the present invention, the protective gas is an inert gas, preferably argon or helium; the flow rate of the protective gas is 20 to 70 sccm, preferably 30 to 50 sccm, and more preferably 50 sccm; the annealing time is 5 to 20 hours, preferably 10 hours; the annealing temperature is 150 to 200° C., preferably 180° C. The heating rate from room temperature to the annealing temperature is 1 to 10° C. / min, preferably 5° C. / min.
[0033] The present invention also provides a lithium metal negative electrode, including a negative electrode current collector and a negative electrode active material layer loaded on the surface of the negative electrode current collector, wherein the raw materials for preparing the negative electrode active material layer include the confined sulfur material of the above technical solution as the negative electrode active material, a binder and an organic solvent.
[0034] In the present invention, the negative electrode current collector is preferably a copper foil current collector.
[0035] In the present invention, the binder preferably comprises polyvinylidene fluoride (PVDF). In the present invention, the mass ratio of the confined sulfur material to the binder is preferably 3 to 5:1, more preferably 4:1.
[0036] In the present invention, the organic solvent includes N-methylpyrrolidone (NMP). In the present invention, the mass ratio of the confined sulfur material to the organic solvent is preferably 5 to 10:1, more preferably 7 to 8:1.
[0037] The present invention provides a method for preparing a lithium metal negative electrode of the above technical solution, comprising the following steps: mixing a confined sulfur material, a binder and an organic solvent to obtain a slurry; coating the slurry on the surface of a copper foil current collector and drying the slurry to obtain a lithium metal negative electrode.
[0038] In the present invention, mixing is preferably stirring mixing. The present invention has no particular limitation on the conditions for stirring mixing, as long as the raw materials can be mixed uniformly.
[0039] In the present invention, the coating thickness of the slurry is preferably 20 to 100 μm, more preferably 50 to 100 μm.
[0040] In the present invention, the drying temperature is preferably 60 to 90° C., more preferably 70 to 80° C.; the drying time is preferably 8 to 15 hours, more preferably 10 to 12 hours.
[0041] The present invention provides the confined sulfur material of the above technical solution, the confined sulfur material prepared by the preparation method of the above technical solution, the lithium metal anode of the above technical solution or the lithium metal anode prepared by the preparation method of the above technical solution, and their use in lithium metal batteries.
[0042] The present invention provides a lithium metal battery, comprising a working electrode, a counter electrode and an electrolyte; the working electrode is the lithium metal negative electrode of the above technical solution or the lithium metal negative electrode prepared by the preparation method of the above technical solution; the counter electrode is a lithium foil; the working electrode and the counter electrode are separated by a diaphragm.
[0043] In the present invention, the electrolyte preferably includes an electrolyte and a solvent; the electrolyte includes lithium bis(trifluoromethylsulfonyl)imide and / or lithium bis(fluorosulfonyl)imide salt; the solvent preferably includes a mixed solvent of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DEM), and the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether in the mixed solvent is preferably 1:1.
[0044] In the present invention, the concentration of the electrolyte in the electrolyte solution is preferably 1 M (mol / L).
[0045] In the present invention, the lithium metal battery preferably includes a lithium button cell.
[0046] In the present invention, the electrolyte preferably further comprises an additive, and the additive preferably comprises LiNO3; the concentration of the additive in the electrolyte is preferably 1 to 5 wt%, more preferably 1 to 2 wt%.
[0047] In the present invention, the separator is preferably a Celgrad 2500 separator.
[0048] The technical solution of the present invention is further described below by means of the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application and belong to the scope of protection of the present invention.
[0049] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0050] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0051] Unless otherwise specified in the present invention, the reagents, instruments, equipment, etc. used are all reagents, instruments and equipment conventionally used by technicians in the field. Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the field.
[0052] Example 1
[0053] The specific steps for preparing confined sulfur materials are as follows: elemental sulfur powder and single-walled carbon nanotubes are fully mixed and placed in a high vacuum environment at 3.0×10 -3 Annealing under pa conditions at 650 °C, cooling to room temperature, and collecting black powder. The collected black powder was placed in a tube furnace, with argon (total flow rate of 50 sccm) as the protective gas, heated to 180 °C at a heating rate of 5 °C / min, annealed for 10 h, and cooled to room temperature to confine sulfur powder S@CNTs.
[0054] The confined sulfur powder and polyvinylidene fluoride were added to NMP and stirred evenly, and the obtained slurry was evenly coated on the surface of the copper foil current collector, and dried in a vacuum oven at 80°C for 10 hours to obtain a lithium metal negative electrode. Among them, the mass ratio of confined sulfur to polyvinylidene fluoride was 4:1, the amount ratio of confined sulfur powder to NMP was 1g:50mL, and the coating thickness of the slurry was 50μm.
[0055] A lithium metal negative electrode was used as the working electrode, a lithium foil was used as the counter electrode, a Celgrad2500 separator was used to separate the working electrode and the counter electrode, and 30 μL of electrolyte (1 M LiTFSI dissolved in DOL / DEM volume ratio = 1:1, 1 wt% LiNO3 additive) was added to assemble a button cell.
[0056] Comparative Example 1
[0057] The single-walled carbon nanotube powder and polyvinylidene fluoride were added to NMP and stirred evenly, and the obtained slurry was evenly coated on the surface of the copper foil current collector, and dried in a vacuum oven at 80°C for 10 hours to obtain a lithium metal negative electrode. The mass ratio of the single-walled carbon nanotube powder to the polyvinylidene fluoride was 4:1, the dosage ratio of the single-walled carbon nanotube powder to NMP was 1g:50mL, and the coating thickness of the slurry was 50μm.
[0058] A lithium metal negative electrode was used as the working electrode, a lithium foil was used as the counter electrode, a Celgrad2500 separator was used to separate the working electrode and the counter electrode, and 30 μL of electrolyte (1 M LiTFSI dissolved in DOL / DEM volume ratio = 1:1, 1 wt% LiNO3 additive) was added to assemble a button cell.
[0059] Comparative Example 2
[0060] Sulfur powder was mixed with single-walled carbon nanotubes, placed in a tube furnace, and heated to 180°C at a heating rate of 5°C / min using argon (total flow rate of 50 sccm) as protective gas, annealed for 10 h, and cooled to room temperature to confine sulfur powder S / CNTs.
[0061] The confined sulfur powder and polyvinylidene fluoride were added to NMP and stirred evenly, and the obtained slurry was evenly coated on the surface of the copper foil current collector, and dried in a vacuum oven at 80°C for 10 hours to obtain a lithium metal negative electrode. Among them, the mass ratio of confined sulfur powder to polyvinylidene fluoride was 4:1, the amount ratio of confined sulfur powder to NMP was 1g:50mL, and the coating thickness of the slurry was 50μm.
[0062] A lithium metal negative electrode was used as the working electrode, a lithium foil was used as the counter electrode, a Celgrad2500 separator was used to separate the working electrode and the counter electrode, and 30 μL of electrolyte (1 M LiTFSI dissolved in DOL / DEM volume ratio = 1:1, 1 wt% LiNO3 additive) was added to assemble a button cell.
[0063] Figure 1 This is a transmission electron microscopy image of the confined sulfur powder prepared in Example 1, indicating that the sulfur chains are in the carbon tubes.
[0064] Figure 2 The optical microscope images of in-situ lithium deposition of Example 1 and Comparative Example 2 show that the lithium deposited in Example 1 is more uniform, while lithium dendrites exist in Comparative Example 2.
[0065] Figure 3 The scanning electron microscope images of lithium deposition of Example 1 (a, c) and Comparative Example 2 (b, d) show that the lithium deposited in Example 1 is more uniform, while lithium dendrites exist in Comparative Example 2.
[0066] Figure 4Electrochemical performance test of Example 1 and Comparative Example 2, where a is the coulombic efficiency of a button half-cell, b is the time-voltage curve of a button symmetrical cell, c is the cycle performance test of a button full cell, d is a physical picture of a soft-pack cell, e is a cycle test of a lithium iron phosphate soft-pack cell, and f is a cycle test of a ternary soft-pack cell. As can be seen from the figure, the electrochemical performance of Example 1 is better and the cycle life is higher.
[0067] Figure 5 The time-of-flight secondary mass spectra of Example 1 and Comparative Examples 1 and 2 indicate that the introduction of sulfur can increase the content of LiF, especially in Example 1, the content of LiF is higher and more evenly distributed. In addition, there are fewer organic components in Example 1.
[0068] Figure 6 The XPS spectra of Example 1 and Comparative Examples 1 and 2 show that the F content in the SEI of Example 1 is higher, and the proportions of C and O are lower, which proves that the LiF content in Example 1 is higher and the organic component content is lower.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A confined sulfur material, characterized in that: It comprises a single-walled carbon nanotube and a sulfur chain in the single-walled carbon nanotube; wherein the sulfur chain is formed by linear connection between single sulfur atoms, and the mass of the sulfur chain accounts for 3-10% of the single-walled carbon nanotube.
2. The method for preparing a confined sulfur material according to claim 1, characterized in that: The elemental sulfur powder and the single-walled carbon nanotube powder are mixed, the mixture is subjected to a primary annealing treatment under high vacuum, taken out and subjected to a secondary annealing treatment in a protective gas, and cooled to obtain a confined sulfur material.
3. The method for preparing a confined sulfur material according to claim 2, characterized in that: During the primary annealing treatment, the vacuum degree is 1~9×10 -3 pa, annealing temperature is 500-700°C, heating rate is 1-10°C / min, and annealing time is 24-60h.
4. The method for preparing a confined sulfur material according to claim 2, characterized in that: During the secondary annealing treatment, the protective gas is an inert gas, and the flow rate of the protective gas is 20-70 sccm; the annealing temperature is 150-200°C, the heating rate is 1-10°C / min, and the annealing time is 5-20h.
5. The use of a confined sulfur material according to claim 1, characterized in that: The confined sulfur material is applied to lithium metal batteries.
6. The use of a confined sulfur material according to claim 5, characterized in that: The confined sulfur material is used to prepare a lithium metal negative electrode, which includes a negative electrode current collector and a negative electrode active material layer loaded on the surface of the negative electrode current collector. The raw materials for preparing the negative electrode active material layer include the confined sulfur material, a binder and an organic solvent.
7. The use of a confined sulfur material according to claim 6, characterized in that: The negative electrode current collector is a copper foil current collector; the binder is polyvinylidene fluoride; and the organic solvent is N-methylpyrrolidone.
8. The use of a confined sulfur material according to claim 6, characterized in that: The mass ratio of the confined sulfur material to the binder is 3 to 5:1; the mass ratio of the confined sulfur material to the organic solvent is 5 to 10:
1.
9. The use of a confined sulfur material according to claim 6, characterized in that: The preparation method of the lithium metal negative electrode is: mixing the confined sulfur material, a binder and an organic solvent to obtain a slurry; coating the slurry on the surface of the negative electrode collector, and obtaining the lithium metal negative electrode after drying.
10. The use of a confined sulfur material according to claim 9, characterized in that: The coating thickness of the slurry is 20 to 100 μm; the drying temperature is 60 to 90° C., and the drying time is 8 to 15 hours.